Stages in the development of a small hydropower project: context and implementation basic criteria (2014)
The purpose of this article is to review and analyze the context and basic requirements to be considered to implement projects of Small Hydro Power, which was performed by collecting information and reviewing of the current state of technology in the country and worldwide, as well as the most efficient and suitable technologies for its implementation. Finally, it raises some stages and engineering studies to follow for successful development of an SHP project and defines the relevant conclusions of the analysis.